Experiential Avoidance and Hyperreflexivity as Variables Associated with Depression: A Process-Based Approach - Blancas-Guillen, Jesus (2023)
Depression is a major public health problem that affects a significant proportion of young adults, such as college students. A process-based approach has been proposed for its study, which seeks to identify transdiagnostic psychological variables that can be the target of change in psychotherapeutic interventions. The purpose of this paper was to analyze the interrelation between a set of process variables (cognitive fusion, rumination, and experiential avoidance), as well as to examine the relationship between each of these variables and depression in 368 college students aged 18–29 years (M = 21.35, SD = 2.36, 77.7% female). Cognitive fusion and rumination were found to comprise an overarching variable termed hyperreflexivity, while experiential avoidance constituted a different construct. By analyzing a structural equation model, it was found that only hyperreflexivity predicted depression significantly. These findings and their possible implications for clinical practice are discussed. Further study of hyperreflexivity as a superordinate variable of relevance to psychopathology is recommended.